Acute effects of a wild green-oat (Avena sativa) extract on cognitive function in middle-aged adults: A double-blind, placebo-controlled, within-subjects trial. (7th February 2017) - Kennedy, David O.; Jackson, Philippa A.; Forster, Joanne; Khan, Julie; Grothe, Torsten; Perrinjaquet-Moccetti, Tania; Haskell-Ramsay, Crystal F.
Abstract : Objectives: A wild green-oats extract (Neuravena ® ) containing a range of potentially bioactive components, including flavonoids and triterpene saponins, has previously been shown to enhance animal stress responses and memory, and improve cognitive performance in humans at a dose of 1600 mg. Methods This double-blind, placebo-controlled, counterbalanced cross-over study assessed the effects of single doses of the green-oat extract (GOE) across a broad range of cognitive domains in healthy adults aged 40–65 years who self-reported that they felt that their memory had declined with age. Participants attended on six occasions, receiving a single dose of either placebo, 800, or 1600 mg GOE on each occasion, with the counterbalanced order of treatments repeated twice for each participant. Cognitive function was assessed with a range of computerized tasks measuring attention, spatial/working/episodic memory, and executive function pre-dose and at 1, 2.5, 4, and 6 hours post-dose. Results The results showed that 800mg GOE increased the speed of performance across post-dose assessments on a global measure including data from all of the timed tasks. It also improved performance of a delayed word recall task in terms of errors and an executive function task (Peg and Ball) in terms of decreased thinking time and overall completion time. Working memory span (Corsi blocks) was also increased, but only on the second occasion that this dose was taken. Discussion These results confirm the acute cognitive effects of GOE seen in previous research, and suggest that the optimal dose lies at or below 800 mg.